2018
DOI: 10.1111/jcal.12271
|View full text |Cite
|
Sign up to set email alerts
|

Profiling sympathetic arousal in a physics course: How active are students?

Abstract: Low arousal states (especially boredom) have been shown to be more deleterious to learning than high arousal states, though the latter have received much more attention (e.g., test anxiety, confusion, and frustration). Aiming at profiling arousal in the classroom (how active students are) and examining how activation levels relate to achievement, we studied sympathetic arousal during two runs of an elective advanced physics course in a real classroom setting, including the course exam. Participants were high s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 52 publications
5
66
0
1
Order By: Relevance
“…Specifically, the students collaborated in pairs to complete an engineering design task, and the authors used hand/wrist movement, electro‐dermal activation, and voice activity detection, for modeling how students engage with the task, in terms of the reasoning strategies the used. Furthermore, in a face to face classroom setting, Pijeira‐Díaz, Drachsler, Kirschner, and Järvelä () utilized the EDA, Galvanic Skin Conductance, temperature and the accelerometer data, to measure simultaneous arousal levels among the students with respect to the students' mood, motivation, affect and collaborative engagement. Results shown that low arousal was the predominant state, whereas all students were never in high arousal states in the classroom, at the same moment.…”
Section: Related Work: Utilizing Multimodal Data To Predict Learning mentioning
confidence: 99%
“…Specifically, the students collaborated in pairs to complete an engineering design task, and the authors used hand/wrist movement, electro‐dermal activation, and voice activity detection, for modeling how students engage with the task, in terms of the reasoning strategies the used. Furthermore, in a face to face classroom setting, Pijeira‐Díaz, Drachsler, Kirschner, and Järvelä () utilized the EDA, Galvanic Skin Conductance, temperature and the accelerometer data, to measure simultaneous arousal levels among the students with respect to the students' mood, motivation, affect and collaborative engagement. Results shown that low arousal was the predominant state, whereas all students were never in high arousal states in the classroom, at the same moment.…”
Section: Related Work: Utilizing Multimodal Data To Predict Learning mentioning
confidence: 99%
“…These devices can shed light on physiological reactions and learning processes that are not explicitly stated in existing theoretical frameworks (Azevedo and Gašević in press). Yet, the scarce amount of studies that have used such sensors in the context of collaborative learning are promising, indicating that they can, for example, track learning challenges (Malmberg et al 2019), predict learning outcomes (Pijeira-Díaz et al 2018), and indicate sharing among group members in monitoring (Haataja, Malmberg, & Järvelä, 2018). That is why it is highly appealing to not only investigate what students verbally express in a learning situation, but to also study the synchrony across individual physiological reactions, invisible to normal human observation and underlying these non-verbal expressions.…”
Section: Collaborative Learning and Physiological Synchronymentioning
confidence: 99%
“…From these data streams, a wide range of higher level features can be inferred including affect, attention, cognitive processing, stress and fatigue. Thus, MMLA may be applicable in a wide range of educational contexts including face-to-face interactions without technological aids (Di Mitri et al, 2017;Pijeira-Díaz, Drachsler, Kirschner, & Järvelä, 2018;Spikol et al, 2018), face-to-face technology enhanced learning (Liu et al, 2016;Viswanathan & VanLehn, 2017b) and online learning (Le, Pardos, Meyer, & Thorp, 2018). Within MMLA, many different combinations of data streams have been explored but it is not clear what makes the different combinations impactful for collaborative learning.…”
Section: Practitioner Notesmentioning
confidence: 99%